Non-organ confined stage and upgrading rates in exclusive PSA high-risk prostate cancer patients - Hoeh, Benedikt; Flammia, Rocco S; Hohenhorst, Lukas; Sorce, Gabriele; Chierigo, Francesco; Tian, Zhe; Saad, Fred; Gallucci, Michele; Briganti, Alberto; Terrone, Carlo; Shariat, Shahrokh F; Graefen, Markus; et al. (The Prostate, 2022)
BACKGROUND: The pathological stage of prostate cancer with high-risk prostate-specific antigen (PSA) levels, but otherwise favorable and/or intermediate risk characteristics (clinical T-stage, Gleason Grade group at biopsy [B-GGG]) is unknown. We hypothesized that a considerable proportion of such patients will exhibit clinically meaningful GGG upgrading or non-organ confined (NOC) stage at radical prostatectomy (RP). MATERIALS AND METHODS: Within the Surveillance, Epidemiology, and End Results database (2010-2015) we identified RP-patients with cT1c-stage and B-GGG1, B-GGG2, or B-GGG3 and PSA 20-50 ng/ml. Rates of GGG4 or GGG5 and/or rates of NOC stage (≥ pT3 and/or pN1) were analyzed. Subsequently, separate univariable and multivariable logistic regression models tested for predictors of NOC stage and upgrading at RP. RESULTS: Of 486 assessable patients, 134 (28%) exhibited B-GGG1, 209 (43%) B-GGG2, and 143 (29%) B-GGG3, respectively. The overall upgrading and NOC rates were 11% and 51% for a combined rate of upgrading and/or NOC stage of 53%. In multivariable logistic regression models predicting upgrading, only B-GGG3 was an independent predictor (odds ratio [OR]: 5.29; 95% confidence interval [CI]: 2.21-14.19; p < 0.001). Conversely, 33%-66% (OR: 2.36; 95% CI: 1.42-3.95; p = 0.001) and >66% of positive biopsy cores (OR: 4.85; 95% CI: 2.84-8.42; p < 0.001), as well as B-GGG2 and B-GGG3 were independent predictors for NOC stage (all p ≤ 0.001). CONCLUSIONS: In cT1c-stage patients with high-risk PSA baseline, but low- to intermediate risk B-GGG, the rate of upgrading to GGG4 or GGG5 is low (11%). However, NOC stage is found in the majority (51%) and can be independently predicted with percentage of positive cores at biopsy and B-GGG.
Keywords: Neoplasm Staging; lidé; staging nádorů; stupeň nádoru; prostatický specifický antigen; Prostate-Specific Antigen; Male; Prostatectomy; Prostate; Neoplasm Grading; nádory prostaty; Prostatic Neoplasms; Humans; mužské pohlaví; prostata; prostatektomie